Genome-Wide Characterization and Anthocyanin-Related Expression Analysis of the B-BOX Gene Family in Capsicum annuum L. - Wang, Jin; Yang, Guangbin; Chen, Ying; Dai, Yao; Yuan, Qiaoling; Shan, Qingyun; Pan, Luzhao; Dai, Li; Zou, Xuexiao; Liu, Feng; Xiong, Cheng (Frontiers in Genetics, 2022)
The transcription factors, B-box (BBX), belong to a subfamily of the zinc finger family of proteins and exhibit multiple biological functions in plant growth, development, and abiotic stress response pathways. In this study, a total of 23 CaBBX members were identified using the pepper reference genome database. According to the gene structure, conserved domains, and the phylogenetic tree, 23 CaBBX genes were divided into four groups, wherein the analysis of the promoter region indicated the presence of cis-acting elements related to plant development, hormones, and stress response. Interspecies collinearity analysis showed that the CaBBXs had three duplicated gene pairs, and the highest gene density was found on chromosomes 2 and 7. Transcriptome RNA-seq data and quantitative polymerase chain reaction (qRT-PCR) analysis of pepper plants spanning the entire period showed that more than half of the CaBBX genes were widely expressed in diversity tissues of pepper. Co-expression network analysis indicated that the CaBBXs and the anthocyanin structural genes had a close co-expression relationship. Thus, it was reasonably speculated that the CaBBX genes may be involved in the regulation of anthocyanin biosynthesis. Overall, this study involved the genome-wide characterization of the CaBBX family and may serve as a solid foundation for further investigations on CaBBX genes involved in the anthocyanin synthesis mechanisms and development in pepper.